2011
DOI: 10.1111/j.1365-3113.2011.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual dissection using phase‐contrast X‐ray synchrotron microtomography: reducing the gap between fossils and extant species

Abstract: Abstract. Fossils provide excellent opportunities for bringing to light evolutionary trends, and testing phylogenetic hypotheses. However, the difficulty in accessing internal structures limits the provision of accurate descriptions, and thus limits the comparison of fossil specimens with extant fauna. The virtual dissection of amber fossils by propagation phase-contrast X-ray synchrotron microtomography (PPC-SRμCT) allows incomparable possibilities for the visualization of genital structures, which are of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Deeper examination of Amplectister internal characters through micro-CT scanning (e.g. Perreau and Tafforeau 2011, Riedel et al 2012) would be particularly informative, as some Saprininae apomorphies are found in the genitalia (Lackner 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Deeper examination of Amplectister internal characters through micro-CT scanning (e.g. Perreau and Tafforeau 2011, Riedel et al 2012) would be particularly informative, as some Saprininae apomorphies are found in the genitalia (Lackner 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The potential of µCT has been demonstrated before, but in taxonomic practice circumstances differ from unique experiments designed to show the capabilities of this technique (Lak et al ., 2008; Perreau & Tafforeau, 2011). The examination of holotypes of previously described species is especially difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusions in amber are usually devoid of compression artefacts and allow examination of fine details, but often the amber is not clear, the view is obscured by bubbles or cracks, and the specimen may only be observed from one aspect. Synchrotron microtomography (µCT) is a relatively new technique to overcome some of these limitations (Lak et al ., 2008; Dunlop et al ., 2011; Perreau & Tafforeau, 2011). It is here used to study features in specimens of relatively poor preservation, in particular the holotype of Sayrevilleus grimaldii Gratshev & Zherikhin, a species so far only known from this single inclusion in New Jersey amber.…”
Section: Introductionmentioning
confidence: 99%
“…Donoghue et al (2006) investigate fossilized embryos, whereas Tafforeau et al(2006) cover a wide range of fossils. More recently, Gai et al (2011) characterized a fossil of a jawless fish using synchrotron-based micro-CT. Other types of fossils include animals which have been preserved in amber , such as spiders (Bosselaers et al, 2010;Penney et al, 2007), beetles (Perreau and Tafforeau, 2011), pseudoscorpions ( Figure 9, which shows in high detail the right chelal fingers of the Pseudogarypus synchrotron Henderickx et al, 2012 at a reconstructed voxel size of 0.667³ µm³) (Henderickx et al, 2006;Henderickx et al, 2012) and earwigs (Perrichot et al, 2011). Other than these natural artefacts, man-made prehistoric objects are the subject of the research of Abel et al (2011).…”
Section:  Morphological Characterization Of Fossilsmentioning
confidence: 99%